2020
DOI: 10.1101/2020.05.21.109835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systemic Effects of Missense Mutations on SARS-CoV-2 Spike Glycoprotein Stability and Receptor Binding Affinity

Abstract: The spike (S) glycoprotein of SARS-CoV-2 is responsible for the binding to the permissive cells.The receptor-binding domain (RBD) of SARS-CoV-2 S protein directly interacts with the human angiotensin-converting enzyme 2 (ACE2) on the host cell membrane. In this study, we used computational saturation mutagenesis approaches, including structure-based energy calculations and sequence-based pathogenicity predictions, to quantify the systemic effects of missense mutations on SARS-CoV-2 S protein structure and func… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“… 59 Notwithstanding, certain residues of the RBD have also been deemed indispensable for the efficient recognition of human ACE2. 79 , 90 , 91 On the contrary, Ou et al 77 have reported that mutations in the RBD of SARS-CoV-2 observed from strains with different geographical distributions actually enhance the binding to ACE2, indicating that some RBD polymorphs might even be more infectious and hence increase the diffusion of the pandemic.…”
Section: Sars-cov-2 Spike Glycoprotein: Structure and Dynamics Of Cormentioning
confidence: 99%
“… 59 Notwithstanding, certain residues of the RBD have also been deemed indispensable for the efficient recognition of human ACE2. 79 , 90 , 91 On the contrary, Ou et al 77 have reported that mutations in the RBD of SARS-CoV-2 observed from strains with different geographical distributions actually enhance the binding to ACE2, indicating that some RBD polymorphs might even be more infectious and hence increase the diffusion of the pandemic.…”
Section: Sars-cov-2 Spike Glycoprotein: Structure and Dynamics Of Cormentioning
confidence: 99%
“…Several amino acid changes detected in the haplotypes present in our analysis are part of the RBD (V367F, S477N, N439K, T478I, and A522S). From these amino acid changes, positions 367 and 439 were associated with the binding affinity of RBD (Teng et al 2020; Yi et al 2020). Additionally, the mutation L5F in the signal peptide was present in 3.3% of members belonging clade V (Korber et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, a broad mutation spectrum of SARS-CoV-2 has been observed, which could lead to vaccine and drug resistance [ 77. , 78. , 79.…”
Section: Challenges In the Successful Development Of Neutralizing Antmentioning
confidence: 99%